Tuberculosis associated with Triplet therapy for lung cancer. Issue 7 (14th May 2020) - Crawley, Danielle; Breen, Ronan A; Elkington, Paul T; Karapanagiotou, Eleni
Abstract : We report the first case of TB associated with triplet therapy (chemotherapy and immunotherapy concurrently) for lung cancer, developing just 44 days after treatment initiation. We feel that several important learning points arise from the discussion that are likely to be very relevant to the broad readership of Thorax, and have important clinical and scientific implications. In the three discussion paragraphs, we highlight that: 1) Triplet therapy is now standard first-line treatment for inoperable lung cancer. 2) TB reactivation is increasingly recognised as an adverse effect of immune checkpoint inhibition, but sending diagnostic samples is critical to avoid a missed diagnosis. 3) These insights from novel cancer immunotherapies are challenging the traditional views of the host-pathogen interaction in TB, with wide implications for future control strategies. We propose that the cases reported in the literature are likely to be the tip of the iceberg as most people with lung cancer managed with antiprogrammed death-1 agents who develop new lung lesions will be treated with standard antibiotics and then palliated when they do not respond.